The combined employment effects of minimum wages and labor market regulation: A meta-analysis - Bernhard Boockmann (Institute for the Study of Labor (IZA), 2010)
This paper provides a meta-analysis of 55 empirical studies estimating the employment effects of minimum wages in 15 industrial countries. It strongly confirms the notion that the effects of minimum wages are heterogeneous between countries. As possible sources of heterogeneity, it considers the benefit replacement ratio, employment protection and the collective bargaining system. While the results are in line with theoretical expectations, the degree to which they are robust differs across these institutions.
Keywords: J38; J20; C12; 330; Minimum wage; regulation; employment; meta-analysis; Mindestlohn; Arbeitsmarktpolitik; Wirkungsanalyse; Beschäftigungseffekt; Meta-Analyse; Industriestaaten